Modeling and Simulation of Virtual Clay Pigeon shooter Training System - Jin Yanxia; Shi Zhibin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As a popular sports event, clay pigeon uses real guns and bullets as its tools. To improve the training effect, reduce its cost and danger, the development of a real-time interactive and perceptive virtual training system by using simulation technology becomes urgent. This system uses Visual C++、Vega、Creator as its development platform to conduct modeling and simulation of clay pigeon’s and grapeshot ‘s flying path and the collision effect of the two objects. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3421